Targeting Leukocyte Trafficking for the Treatment of Inflammatory Bowel Disease. Issue 1 (2nd December 2014) - Arseneau, KO; Cominelli, F
Abstract Inflammatory bowel disease (IBD) is a chronic immune‐mediated inflammatory disease of the intestine that includes both Crohn's disease and ulcerative colitis, and afflicts nearly 1 million people throughout North America. As our understanding of IBD pathogenesis grows, several new therapies have been developed that use monoclonal antibodies to specifically target key mediators and biological pathways implicated in IBD immune dysfunction. One important pathway involves leukocyte trafficking and infiltration into the affected intestinal tissues. This review provides a summary of the different therapies that have been developed to inhibit leukocyte trafficking to the inflamed gut, and evaluates the relative safety and efficacy of these novel drugs within the context of existing medical therapies for IBD.